Indonesian Version of WHO-5 Well-being Index Amidst COVID-19 Pandemic Settings: Scale Validation and Standardisation - Rena Latifa; Kay Chang; Andrian Liem; Natris Idriyani; Adiyo Roebianto; Muthia Rahmah; Valendra Granitha Shandika Puri (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2023)
The 5-item World Health Organization Well-Being Index (WHO-5) is a frequently used brief standard measure in large-scale clinical studies. However, no research specifically on the validity test of WHO-5 was found in Indonesia before the pandemic. This study aims to test the validity of the Indonesian version of the 5-item WHO-5 in the COVID-19 pandemic setting. The online survey was used to collect data from February-2021 to September 2021. 1,084 Indonesians who were directly or indirectly affected by COVID-19 completed the survey. The scale was validated with Confirmatory Factor Analysis (CFA) and Item Response Theory (IRT). The CFA and IRT analysis showed that the WHO-5 is valid. Thus, the WHO-5 is a short questionnaire that consists of five non-invasive questions adequate to measure the psychological well-being of the Indonesian sample, especially during the COVID-19 Pandemic, and could be used in other pandemics or crises.